Pro-inflammatory cytokines disrupt in vitro preantral follicle development by targeting granulosa and theca cell functions - Shirafuji, Aya; Orisaka, Makoto; Shimizu-Mizuno, Natsumi; Uesaka, Miki; Fujita, Yuko; Mizuno, Katsutoshi; Fujita, Masayuki; Miyazaki, Yumiko; Onuma, Toshimichi; Tsuyoshi, Hideaki; Mizutani, Tetsuya; Yoshida, Yoshio (Frontiers in Endocrinology, 2026)
BackgroundChronic low-grade inflammation is increasingly recognized as a contributing factor to female infertility. Elevated levels of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 are observed in ovarian conditions including obesity, polycystic ovary syndrome, endometriosis, and reproductive aging. However, how these cytokines affect early follicular development remains poorly understood. This study aimed to elucidate the effects of TNF-α, IL-1β, and IL-6 on granulosa cell (GC) and theca cell (TC) function during the preantral-to-antral transition—a critical checkpoint that determines follicular growth or atresia.MethodsWe employed a three-dimensional culture model using mechanically isolated rat preantral follicles. Follicles were treated with TNF-α, IL-1β, or IL-6 in the presence or absence of FSH. We assessed follicular growth, steroid production, gene expression, reactive oxygen species accumulation, and type III collagen deposition using ELISA, quantitative PCR, and immunofluorescence analyses.ResultsIn the absence of FSH, none of the cytokines altered GC volume; however, TNF-α significantly suppressed FSH-induced GC proliferation. All three cytokines—TNF-α, IL-1β, and IL-6—increased TC volume without enhancing androgen production. FSH-stimulated estradiol and testosterone synthesis was markedly impaired, accompanied by downregulation of key steroidogenic genes including Fshr, Cyp19a1, Lhcgr, Cyp11a1, and Cyp17a1. TNF-α and IL-1β elevated oxidative stress levels in GC. All cytokines upregulated Tgfb1 expression, while IL-1β and IL-6 induced mild type III collagen deposition in the TC layer, suggesting early activation of fibrotic signaling. Notably, follicles with multi-layered TC structures exhibited partial resistance to TNF-α–induced oxidative stress and GC dysfunction.ConclusionPro-inflammatory cytokines impair early follicular development by disrupting GC and TC function through gonadotropin resistance, oxidative stress, and fibrotic signaling. These findings provide a novel insight into how chronic inflammation compromises ovarian function, and suggest that preserving the follicular microenvironment—particularly TC integrity—may be key to mitigating cytokine-induced follicular dysfunction in inflammatory reproductive disorders.